A importância do território para populações tradicionais, e a luta pela permanência no local - SILVA, Rodrigo de Sousa (2024)
This work aims to report how was the entire trajectory of research work developed in the Nova Olinda community, report step by step how the whole process took place, the difficulties and challenges encountered, also addresses the concepts of territory for Western society and for local residents and what is the importance of living in their place of origin.